2006
DOI: 10.1210/er.2005-0007
|View full text |Cite
|
Sign up to set email alerts
|

Insulin Resistance and Atherosclerosis

Abstract: The epidemic of obesity in the developed world over the last two decades is driving a large increase in type 2 diabetes and consequentially setting the scene for an impending wave of cardiovascular morbidity and mortality. It is only now being recognized that the major antecedent of type 2 diabetes, insulin resistance with its attendant syndrome, is the major underlying cause of the susceptibility to type 2 diabetes and cardiovascular disease. In metabolic tissues, insulin signaling via the phosphatidylinosito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
227
1
8

Year Published

2008
2008
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 285 publications
(241 citation statements)
references
References 187 publications
5
227
1
8
Order By: Relevance
“…Although the etiology is not completely understood, the extracellular matrix (ECM) remodeling has a critical role for the onset of vascular diseases (1). The glycosaminoglycan hyaluronan (HA), other proteoglycans, including versican, and matrix metalloproteinases accumulate within the neointima and strongly induce SMC growth, motility, LDL binding, and monocyte recruitment, which promotes vessel thickening (2)(3)(4)(5). The crucial role of HA has been demonstrated in transgenic animals overexpressing HAS2 as well as in mice lacking the HA receptor CD44, which are prone to and protected from atherosclerosis, respectively (6,7).…”
mentioning
confidence: 99%
“…Although the etiology is not completely understood, the extracellular matrix (ECM) remodeling has a critical role for the onset of vascular diseases (1). The glycosaminoglycan hyaluronan (HA), other proteoglycans, including versican, and matrix metalloproteinases accumulate within the neointima and strongly induce SMC growth, motility, LDL binding, and monocyte recruitment, which promotes vessel thickening (2)(3)(4)(5). The crucial role of HA has been demonstrated in transgenic animals overexpressing HAS2 as well as in mice lacking the HA receptor CD44, which are prone to and protected from atherosclerosis, respectively (6,7).…”
mentioning
confidence: 99%
“…Cholesterol-lowering and anti-hypertensive effects of flavonoids have also been described [4]. The central component of the oxidation hypothesis of atherogenesis is that oxidative modification of LDLs provides an immunogenic stimulus for monocyte recruitment to the vessel wall and phagocytic uptake of oxidized LDL by macrophages [14]. Extensive oxidation of LDLs leads to its aggregation [15,16] and that both of these modified forms of LDLs are present in the atherosclerotic lesion.…”
Section: Introductionmentioning
confidence: 99%
“…Even though some studies have demonstrated that an acute increase in O-GlcNAcylation improves cell survival (10) and reduces the myocardial infarct size induced by ischemia (11), sustained increase of O-GlcNAc levels has been implicated as a pathogenic contributor to glucose toxicity and insulin resistance (8,9). Vascular smooth muscle cells (VSMCs) in the blood vessels play an important role in diabetes-induced development of arteriosclerosis and hypertension (12). Increased HBP flux may influence vascular remodeling, as it can differentially modify the rates of cell growth and cell death of different cell types in the vasculature, leading to hyperplasia of VSMCs as well as increased risk for atherosclerosis (13).…”
Section: Introductionmentioning
confidence: 99%